2016
DOI: 10.1002/2016gl068999
|View full text |Cite
|
Sign up to set email alerts
|

Extensive release of methane from Arctic seabed west of Svalbard during summer 2014 does not influence the atmosphere

Abstract: We find that summer methane (CH4) release from seabed sediments west of Svalbard substantially increases CH4 concentrations in the ocean but has limited influence on the atmospheric CH4 levels. Our conclusion stems from complementary measurements at the seafloor, in the ocean, and in the atmosphere from land‐based, ship and aircraft platforms during a summer campaign in 2014. We detected high concentrations of dissolved CH4 in the ocean above the seafloor with a sharp decrease above the pycnocline. Model appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 45 publications
11
100
0
2
Order By: Relevance
“…However, Student t testing found that the fraction of oceans sampled had a consistently large p value across the season (p > 0.05), suggesting that footprint sensitivity in oceans was not correlated with CH 4 . This is consistent with a recent study of summertime sea-air flux of CH 4 around Svalbard, Norway, which measured low boundary layer CH 4 enhancements despite substantial surface ocean concentrations of CH 4 from subsea clathrate deposits in the high Arctic (Myhre et al, 2016). Boltz.-Arrh., Lin.…”
Section: Mountain and Ocean Eco-regionssupporting
confidence: 80%
“…However, Student t testing found that the fraction of oceans sampled had a consistently large p value across the season (p > 0.05), suggesting that footprint sensitivity in oceans was not correlated with CH 4 . This is consistent with a recent study of summertime sea-air flux of CH 4 around Svalbard, Norway, which measured low boundary layer CH 4 enhancements despite substantial surface ocean concentrations of CH 4 from subsea clathrate deposits in the high Arctic (Myhre et al, 2016). Boltz.-Arrh., Lin.…”
Section: Mountain and Ocean Eco-regionssupporting
confidence: 80%
“…A comprehensive study by Myhre et al (2016) calculated a median methane flux of only 3 µmol m 2 d −1 , which is supported by a median methane flux of 2 µmol m 2 d −1 for the coastal waters of Svalbard (Mau et al, 2017), and this value lies within the previously reported range of 4 to 20 µmol m 2 d −1 ; Table 5). For the North American Arctic Ocean and its shelf seas, rather low methane fluxes of 1.3 µmol m 2 d −1 have been reported (Fenwick et al, 2017).…”
Section: Diffusive Methane Fluxsupporting
confidence: 52%
“…The top-down calculations of methane flux seem to be higher than the bottom-up calculation, at 94 and 200-300 µmol m 2 d −1 , respectively Myhre et al, 2016). Ebullition of methane from the sediment in this area is also reported, resulting in methane fluxes that are 1-2 orders of magnitude higher than the calculated values (Table 5).…”
Section: Diffusive Methane Fluxmentioning
confidence: 77%
See 2 more Smart Citations